THE MAN IN THE BLACK-AND-WHITE «FRAME» OF VASYL STEFANYK'S PROSE - Kyrylyuk, S. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article pays attention to peculiarities of Vasyl Stefanyk’s prose written in the general cultural context of time. Important role is given to the person in the black and white “frame” of the Ukrainian prose in the period fin de siècle, their gestures, facial expression, glance through which the author depicts the character. The object of attention is Vasyl Stefanyk’s novellas. The research is based on the principles of analytical anthropology, theory and history of development of cinema.